Analisis Penggunaan Antibiotik Profilaksis pada Pasien Bedah Sesar (Sectio Caesarea) - Monica, Anggi; Ramdhany, Muh. Wisda Praja; Putra, Made Sandhi Pratama (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2024)
Cesarean section (C-section) is a delivery method involving surgical incisions on the abdomen and uterus. C-section carries the risk of postoperative complications such as surgical site infection (SSI). Hence, there is a need for prophylactic antibiotic administration. Prophylactic antibiotics are used to prevent infection complications resulting from surgery and are administered before, during, and after the operation. The selection of antibiotics is crucial because inappropriate antibiotic use can lead to resistance. This research aims to analyze the usage profile and evaluate the rationality of prophylactic antibiotics in C-section procedures at Wira Bhakti Hospital. This study is a non-experimental descriptive research in which retrospective data collection was conducted in the form of medical records of C-section patients. Also, the rationality assessment was performed using the Gyssens method. The research findings show that the most used antibiotics are ceftriaxone (70.6%), cefotaxime (25%), and cefoperazone (4.4%). Meanwhile, the rationality assessment using Gyssens' method shows that all prophylactic antibiotic use falls under the categories of IVA (more effective alternative) and IVD (narrower spectrum alternative).